Chemical proteomic analysis of palmostatin beta-lactone analogs that affect N-Ras palmitoylation. (1st December 2021) - Suciu, Radu M.; Luvaga, Irungu K.; Hazeen, Akram; Weerasooriya, Chulangani; Richardson, Stewart K.; Firestone, Ari J.; Shannon, Kevin; Howell, Amy R.; Cravatt, Benjamin F.
Graphical abstract: Abstract: S -Palmitoylation is a reversible post-translational lipid modification that regulates protein trafficking and signaling. The enzymatic depalmitoylation of proteins is inhibited by the beta-lactones Palmostatin M and B, which have been found to target several serine hydrolases. In efforts to better understand the mechanism of action of Palmostatin M, we describe herein the synthesis, chemical proteomic analysis, and functional characterization of analogs of this compound. We identify Palmostatin M analogs that maintain inhibitory activity in N-Ras depalmitoylation assays while displaying complementary reactivity across the serine hydrolase class as measured by activity-based protein profiling. Active Palmostatin M analogs inhibit the recently characterized ABHD17 subfamily of depalmitoylating enzymes, while sparing other candidate depalmitoylases such as LYPLA1 and LYPLA2. These findings improve our understanding of the structure–activity relationship of Palmostatin M and refine the set of serine hydrolase targets relevant to the compound's effects on N-Ras palmitoylation dynamics.